Toxic metal phytoremediation using high biomass non-hyperaccumulator crops: New possibilities for bioenergy resources - Souza, Lucas Anjos; Camargos, Liliane Santos [UNESP]; Carvalho, Marcia Eugenia Amaral (My University, 2018)
Human development has brought worldwide problems regarding environmental pollution since our plant, animal and industrial production systems inject a high diversity of organic and inorganic pollutants into fresh underground water, seas, air and soil. Currently, toxic metals are included in the class of the most frequent soil pollutants, and there is no prediction for decreasing their releasing in the environment. This kind of pollutant is of great importance because they cannot be metabolized or degraded and some of them are essential elements to plant development (Fe, Zn, Cu and Mn), whereas others are non-nutrient and it is extremely toxic to plants, such as Cd, Hg and Pb, which can be commonly found in wastes and mining byproducts. In this context, phytoremediation rises as a promising phytotechnology that can recover toxic metal from polluted soil and water. Particular plant species can uptake and accumulate high amounts of toxic metals in their tissues, the so called hyperaccumulators. These plants are valuable models for understanding the biochemical, physiological and molecular mechanisms that confer them tolerance to such stressful conditions. However, it is quite impossible to use them as phytoremediators in field scales, since they are very small and low biomass producers. For this reason, we will bring a different insight in this chapter, which is the use of high biomass non-hyperaccumulator plant species as toxic metal phytoremediators. We will consider for such approach, the physiology, biochemistry and molecular features that are related to metal tolerance in distinct species, with special attention to legumes and grasses that can be used as cover crops whose biomass can be further used for bioenergetic purpose.
Keywords: Bioenergy; Heavy metals; Phytotechnology